Financial and managerial aspects in human resource management : a practical guide - Pepple, Dennis; Zhang, Crystal (Emerald Publishing, 2021)
Financial and Managerial Aspects in HRM: A Practical Guidebreaks new ground by being the first to compile the everyday management and financial decisions of HR managers in a single book. It is an essential resource for understanding core practical HRM issues in the modern workplace.